A new species of Stenomicra Coquillett (Diptera: Periscelididae) from the Brazilian Amazon and its life history - Gomes, Eliane Solar; Ale-Rocha, Rosaly; Keppler, Ruth Leila Ferreira (Zootaxa, 2018)
A new species of Stenomicra is described for the Neotropical Region, from phytotelmata of Araceae at an urban forest fragment in the city of Manaus, state of Amazonas, Brazil. Morphological descriptions of the immatures and the adults (male and female) are provided, together with biological information on the life cycle of the species and its “host” plant.